Analysis of Health Protocol Implementation Through UTAUT (Unified Theory of Acceptance and Use of Technology) Model in Trenggalek DistrictMODEL IN TRENGGALEK DISTRICT - Daniati, Reni; Andini, Rizqi Aulia Kusuma; Ni'am, Achmad Chusnun; Utami, Rahayu Putri; Mirzayanti, Yustia Wulandari; Prasetya, Kevin Daffa; Agatha, Marsha Savira (2477 - 6165, 2024)
The COVID-19 pandemic has introduced significant behavioral changes driven by adopting health protocols known as the 5M measures—mask-wearing, handwashing, maintaining physical distance, limiting mobility, and avoiding crowds. This study evaluates the implementation of the 5M health protocols in Trenggalek and Bendungan Districts, representing urban and rural areas, respectively. Utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) model, modified with Clean and Healthy Behavior (PHBS) constructs, this research examines community awareness and adherence to 5M protocols. A survey involving 758 respondents from both districts was conducted during the pandemic to assess factors influencing compliance. The findings highlight that social influence through counseling, advertisements, and posters plays a pivotal role in shaping behavioral intentions related to protocol adherence. Furthermore, these intentions directly influence actual behavior, reinforcing sustained compliance with the 5M measures. Notably, urban and rural contexts demonstrated similar patterns, underscoring the universal impact of social influence regardless of geographic setting. This study concludes that strengthening community engagement and targeted social campaigns can enhance public health resilience and preparedness for future pandemics by fostering sustainable health-conscious behavior.